Information Technology Crime - Amiruddin; Haziq, M. Haziq Annabil; Rio Ananata Putra Panjaitan; Budi Hasiholan Sitanggang (Cattleya Darmaya Fortuna, 2024)
Information technology crime, or cybercrime, has become a serious threat as technology develops and reliance on the internet increases. These crimes include various illegal acts such as data theft, privacy violations, and attacks on systems. To deal with these threats requires in-depth understanding and mitigation measures that include cybersecurity training, updated security policies, and the use of advanced technology. Cooperation between the public and private sectors is also important in building an effective defense strategy. Education and training in cybersecurity must be improved to prepare future generations to face these digital challenges.